PENGARUH METODE KANGURU TERHADAP STABILITIS SUHU TUBUH BAYI DI RUANG PERINATOLOGI RUMAH SAKIT UMUM DAERAH BENGKALIS - Heriyeni, Heni (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Infant temperatures is low causedmetabolic process and physiological to be late. Speedrespiration and throb heart very late, pressure of low blood, The speed respiratory andthrob heart greatly slowed, low blood pressure and consciousness ieght (BBLR) early 30minutes the infants experience temperature decreased 3-4°C. If this conditioncontinuously and it’s not get handling so can cause death in the newborn.Data healthofficial of Bengkalis regency for year 2016. Number of infant death( AKB) as much as 20casewith cause death infant low weight (BBLR).In 2017 number of infant death(AKB) asmuch as 6 case. The one of alternative to infant body temperature stability with kangaroomethod. The purpose research to knows the affect of kangaroo method on infant bodytemperature stability. The types of research is quantitative analysis with QuasyExperimental. This research conducted in the perinatology room bengkalis hospitalgeneral district on December 20170 to August 2018 ,by using Purposive Sampling . Themethod of research used is non parametric test such as wilcoxon test. The instrumentthisresearch areusing page observation and thermometer . The result research has beendo to 34 respondent were given treatment of kangaroo method for 1 day will be gettingchanges in average body temperature before given treatment kangaroo method in theamount of 35.45°C while after 37.10°C . The result test of wilcoxon non parameticwill begot is affect of kangaroo method on stability infant body temperature in the perinatologyroom Bengkalis hospital general district with p- 0.000. So, it concluded the kangaroomethod has a strong affect to increasing infant's body temperature. It’s hoped cancontinuously toimprove the mother’s knowledge in giving treatment of kangaroo methodon infants to increase or stabilize the infant’s body temperature as well as improve thebouding between mother and her baby.Key word :Affect, Kangaroo Method, Temperature Stability